2012
DOI: 10.1063/1.4705398
|View full text |Cite
|
Sign up to set email alerts
|

Lateral energy band profile modulation in tunnel field effect transistors based on gate structure engineering

Abstract: Choosing novel materials and structures is important for enhancing the on-state current in tunnel field-effect transistors (TFETs). In this paper, we reveal that the on-state performance of TFETs is mainly determined by the energy band profile of the channel. According to this interpretation, we present a new concept of energy band profile modulation (BPM) achieved with gate structure engineering. It is believed that this approach can be used to suppress the ambipolar effect. Based on this method, a Si TFET de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…For example, the transfer curve of the HMG TFET with WFgatel = 4.1eV and WFgate2= 4.5eV is almost the same as that of the HMG TFET with WFgatel = 4.3eV and WFgate2 = 4.7eV; the only difference is their V tum-on [12]. Therefore, in our study, WFgatel was set at 4.1eV, and WFgate2 varied.…”
Section: Results Andmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, the transfer curve of the HMG TFET with WFgatel = 4.1eV and WFgate2= 4.5eV is almost the same as that of the HMG TFET with WFgatel = 4.3eV and WFgate2 = 4.7eV; the only difference is their V tum-on [12]. Therefore, in our study, WFgatel was set at 4.1eV, and WFgate2 varied.…”
Section: Results Andmentioning
confidence: 85%
“…Due to the special gate structure, the energy band profile of the HMG TFET is modulated, and a local minimum in conduction band is formed. Previous simulation results showed this band profile modulation (BPM) effect can lead to an abrupt switching behavior and an improved Ion current of TFETs [12]. Based on this design principle, some novel devices were also proposed [13], [14].…”
mentioning
confidence: 99%
“…26,27) According to this principle, the HMG TFET was proposed, and the literature showed that the device had better subthreshold behavior than singlematerial-gate (SMG) TFET. 20,22) The proposed model was extended to the HMG TFET to check the scalability. As presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8a shows, an ohmic contact is produced at the metal-oxide interface, and massive electrons coming from the metal (Al or Ag) layer are concentrated in a very thin region of the FTO near the interface to form an accumulation layer of majority carrier electrons. However, since Cu has a work function of 4.7 eV [46], when Cu and FTO are brought into contact, massive electrons move from the FTO layer to the Cu layer and a barrier layer is formed at the contact interface, as shown in Fig. 8b, resulting in a lower carrier electron concentration at the interface.…”
Section: Optical Propertymentioning
confidence: 97%
“…After laser irradiation, the sheet resistances of the Al/FTO, Ag/FTO and Cu/FTO films reduce to 5.8, 6.6 and 7.6 X/sq, respectively. The work function of Al (u = 4.1 eV) and Ag (u = 4.1 eV) are smaller than that of FTO (u = 4.4 eV) [46][47][48]. As a consequence, as Fig.…”
Section: Optical Propertymentioning
confidence: 98%